The Concept of Spherical Waves of Higher Education Development Management - Pavlikha, Nataliia; Totska, Olesia (National Interest, 2021)
The aim of the article is to develop the concept of spherical waves of management of higher education development in Ukraine. The concept consists in integration into European Higher Education Area (EHEA) on the basis of five spherical waves: equal interaction of all participants of the educational process; extension of management actions to various spheres of activity of the higher education institution (HEI); interactions with stakeholders; dissemination of management actions at different levels; coverage of all successive phases of the management process. The spherical wave of higher education management within a HEI is defined as a set of certain homogeneous elements (phases, levels, stakeholders, spheres or participants of the educational process), which is targeted management influence from the relevant management center (HEI’s leadership) to achieve strategic, tactical and operational goals of the HEI in the EHEA. The mechanism of involvement of stakeholders in cooperation with the HEI is described.